2021
DOI: 10.1111/jan.14782
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality and distraction cards to reduce pain during intramuscular benzathine penicillin injection procedure in adults: A randomized controlled trial

Abstract: Aim The aim of this study was to determine the effect of using three‐dimensional videos with virtual reality glasses and distraction cards including optical illusion pictures on patients’ pain and satisfaction levels during intramuscular benzathine penicillin injection. Design A randomized controlled trial. Method The study population consisted of 91 patients who were prescribed intramuscular benzathine penicillin medication. The participants were stratified by gender and assigned to three groups (control, vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…We were surprised to observe that a third of patients in the intervention groups removed the video glasses during the procedure, and only 58% would use this technology again. This latter percentage is lower than other studies where 74 to 95% were satisfied, even when no significant effects on anxiety or pain were reached 3–7 . Interestingly, as in other studies, 94% wanted this device to be available for others, although they did not want it for themselves 3,4 …”
mentioning
confidence: 61%
See 2 more Smart Citations
“…We were surprised to observe that a third of patients in the intervention groups removed the video glasses during the procedure, and only 58% would use this technology again. This latter percentage is lower than other studies where 74 to 95% were satisfied, even when no significant effects on anxiety or pain were reached 3–7 . Interestingly, as in other studies, 94% wanted this device to be available for others, although they did not want it for themselves 3,4 …”
mentioning
confidence: 61%
“…We demonstrated that audiovisual distraction with a head-mounted device has no advantageous effect on procedural anxiety and pain among chronic pain patients receiving a pain relief intervention. This is similar to some previous trials, 3,4 but in contrast to some other trials, which did show an anxiety reduction but no pain reduction 5 or conversely only a reduction in pain 6,7 . Possibly the level of distraction was too much as the patients felt ‘out of control’ of their being in a vulnerable position and not knowing what was about to happen: this might also explain a lack of effect among vasectomy patients 3 and obstetric patients undergoing external cephalic version 4 and positive results among patients receiving an intramuscular injection, 6 radiologic intervention 5 or during regular contractions in labor 7 .…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In a retrospective chart review, Chau et al [28] showed the feasibility of using VR during botulinum toxin injections in 14 pediatric patients and reported benefits in the management of procedural pain [28]. In adults, VR also seems to offer advantages in some hospital settings, even in other types of injections, regarding pain, anxiety, and anger management due to the distraction provided by this technology [29][30][31]. However, the effects and feasibility of VR during the intramuscular injection of botulinum toxin in adults presenting with spasticity have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Çocuklarda genellikle antibiyotik, vitamin ve antiemetik gibi ilaçların verilmesinde IM enjeksiyon tercih edilmektedir. 2,3 Çocuklar, erişkinlerden farklı bir bakım ve tedaviye gereksinim duyarlar. Erişkinler ile kıyaslandıklarında biyopsikososyokültürel sınırlılıklardan dolayı tıbbi zarara maruz kaldıklarında ciddi sonuçlarla karşılaşılmaktadır.…”
unclassified